Quality assesment of BAI frozen corned beef and other similar products in the market - Nuesca, Joyce Ramos; Rivera, Lourdes S. (1994.)
ABSTRACT The Bureau of Animal Industry, a government agency wanted to assess the acceptability of their frozen corned beef with similar products, CDO, RICA, nd SWIFT frozen corned beff which are already sold in the market. To determine this, proximate analyses. microbiological test and Quantitative Descriptive Analysis (QDA) were done. The acceptability was further determined by a consumer survey conducted in Quezon City. Major findings of the proximate analyses showed that the pH of BAI frozen corned beef a little variations with CDO, RICA, and SWIFT. The pH was 6.72. Its percentage moisture and crude fat were 52 percent and 11 percent, respectively. BAI was also found to contain 2.93 percent salt. The microbiological examination using Total Plate Count (TPC) and Potato Dextrose Agar (PDA) had indicated that BAI had the same tolerable microbial and mold growth with CDO, RICA and SWIFT. On the other hand, the product profile of the four frozen corned beef showed some difference. BAI was rated highest in the aroma, uniformity in size, corned beef flavor and moistness profiles. BAI also shared the same color profile with RICA. Although BAI was found to be the acceptable in the general acceptability profile. The acceptability of BAI was further assessed with the conduct of a consumer survey test. The consumer survey was done in 8 schools and 4 offices in Quezon City. There were 250 respondents, of which 171 belong to the 13-19 aged group and 79 belonged to the 20-36 aged group. The level of acceptability was determined by nine point hedonic rating and ranking of preference of the four samples. Results of that percentage distribution of the level of acceptability and ranking was greatest in BAI. It was followed by CDO, then RICA and lastly SWIFT. Statistical analysis using Freidman Two-Way Analysis of Variance established a significant difference (α=0.05) on the level of acceptability and ranking preference among the four frozen corned beef. The Page test for Rank Tendency substantiated the ranking sequence, BAI>CDO>RICA>SWIFT.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Frozen meat; Meat and meat products -- Philippines